Islamic Psycho-spiritual Education as a Holistic Solution to Alleviating Extreme Poverty in Indonesia - Dawam, Ainurrafiq; Syaidah, Khasnah (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study explores the role of Islamic education through a psycho-spiritual approach in alleviating extreme poverty in Indonesia. Extreme poverty, which encompasses economic, social, psychological, and spiritual dimensions, requires a holistic approach to empowerment. Islamic education is more than just a transfer of knowledge; it shapes character and positive mentality through values such as patience, sincerity, and social care. This study employs a literature review method with a qualitative approach to analyze how psycho-spiritual education can be part of a sustainable solution. The findings indicate that integrating psycho-spiritual education into poverty alleviation programs can help build individuals’ mental and spiritual resilience. With collaboration between the government, Islamic educational institutions, and community organizations, this approach has the potential to be an effective strategy for addressing the challenges of extreme poverty. This research offers a new perspective on empowering communities through holistic education.AbstrakPenelitian ini mengeksplorasi peran pendidikan Islam melalui pendekatan psikologis spiritual dalam mengentaskan kemiskinan ekstrim di Indonesia. Kemiskinan ekstrim, yang tidak hanya terbatas pada aspek ekonomi tetapi juga mencakup dimensi sosial, psikologis, dan spiritual, memerlukan pendekatan holistik untuk pemberdayaannya. Pendidikan Islam berfungsi lebih dari sekadar transfer pengetahuan, melainkan membentuk karakter dan mentalitas positif melalui nilai-nilai seperti kesabaran, keikhlasan, dan kepedulian sosial. Studi ini menggunakan metode studi pustaka dengan pendekatan kualitatif untuk menganalisis bagaimana pendidikan psikologis spiritual dapat menjadi bagian dari solusi berkelanjutan. Hasil penelitian menunjukkan bahwa integrasi pendidikan psikologis spiritual dalam program pengentasan kemiskinan dapat membantu membangun ketahanan mental dan spiritual individu. Dengan kolaborasi antara pemerintah, lembaga pendidikan Islam, dan organisasi masyarakat, pendekatan ini berpotensi menjadi strategi yang efektif dalam menghadapi tantangan kemiskinan ekstrim. Penelitian ini menawarkan perspektif baru dalam pemberdayaan masyarakat melalui pendidikan yang holistik.  How to Cite: Dawam, A., & Syaidah, K. (2024). Islamic Psycho-spiritual Education as a Holistic Solution to Alleviating Extreme Poverty in Indonesia. TARBIYA: Journal of Education in Muslim Society, 11(1), 93-104. doi:10.15408/tjems.v11i1.42131.